Rectal Bleeding in a Young Infant: Can it be Allergy? Retorragia em Pequeno Lactente: Será Alergia? - Ferreira, Sara Narciso; Cifuentes, Carla; Kullberg, Teresa; Macedo, Laura Sousa de; Levy, Pilar de Quinhones (Gazeta Médica, 2017)
In the exclusively breastfed infants, symptoms associated with food allergy generally may only involve the gastrointestinal tract. The symptoms may begin during the first weeks of life, constituting a warning sign to the pediatrician. Secreted proteins in breast milk are responsible for inducing an inflammation of the colon and rectum by an allergic process non-IgE-mediated. The authors present a case of infancy proctocolitis induced by cow’s milk and soy proteins, in a two-month-old infant, exclusively breastfed, with regression of symptoms after maternal diet. Our goal is to recall this benign disorder which has a clinical diagnosis. Continued breastfeeding should be encouraged. Received: 03/04/2017 - Accepted: 30/05/2017